Os caminhos do sistema de moda: os diálogos com a arte e seus disfarces - Resende, Patrícia Helena Soares Fonseca Rossi de (2014)
This dissertation studies the fashion system development and its relationships with the art field. It analyses how the modern fashion system structure was founded by the Universal Exhibitions and the first department stores. It also shows how the fashion designers Charles Fréderic Worth e Paul Poiret built their artistic images, and states that these relationships were used to give an art status for their work. This research also verifies how the interdisciplinary practices of both Worth and Poiret established standards for the referred practices in contemporary fashion; it analyses the interdisciplinary dialogues present in fashion exhibitions located in art museums. It also considers the Arhem Mode Biennale and its connections with the fashion system and it concludes pointing out the importance of fashion exhibitions for the renewal and perpetuation of the fashion system.